HARGA DAN KUALITAS PRODUK BERPENGARUH TERHADAP MINAT BELI KERUPUK KEMPLANG USAHA KECIL MENENGAH PALEMBANG - Widagdo, Herry; Ayu, Charisma; Pratiwi, Raisa (Fakultas Ekonomi Universitas IBA, 2017)
This research was conducted with the aim to know how the influence of price andproduct quality on the purchasing intention kerupuk kemplang UKM in Palembang city.The type of this research is quantitative descriptive research with data collection throughthe distribution of questionnaires distributed to 150 respondents who have intention toconsume kerupuk kemplang in Palembang city by purposive sampling technique and dataanalysis using multiple regression. The results of this study with simultaneous, the priceand product quality positively influence the purchasing intention kerupuk kemplangPalembang amounted to 4.092 with a significant level of 0.019. Partially, the price doesnot affect the purchasing intention where the variable probability is 0,521>0,05 whilethe product quality can influence the purchasing intention of kerupuk kemplang inPalembang where the variable probability is 0,01 <0,05.